Biochemical protective effect of 1, 25-dihydroxyvitamin D3 through autophagy induction in the MPTP mouse model of Parkinson's disease. Issue 12 (19th August 2015) - Li, Huan; Jang, Wooyoung; Kim, Hee Ju; Jo, Kwang Deog; Lee, Moon Kyu; Song, Sun Hong; Yang, Hyun Ok
<x xml:space="preserve">Abstract</x> In our previous study, the neuroprotective effect of calcitriol was confirmed in SH-SY5Y cells. In this article, we explored whether calcitriol showed neuroprotection in a subchronic 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated mouse model of Parkinson's disease. After mice were treated with MPTP alone or cotreated with MPTP and calcitriol, the substantia nigra pars compacta was dissected, and related protein levels were detected by western blot. Our results suggest that the MPTP-injected mice treated with calcitriol had attenuated tyrosine hydroxylase expression and increased LC3-II conversion compared with those that were not. Above all, calcitriol showed neuroprotection in the MPTP mouse model.